Hubungan Antara Perilaku Merokok dengan Volume Tidal Paru pada Mahasiswa - Siti Fadlilah (STIKES Karya Husada Kediri, 2019)
Background: Smoking behaviors are detrimental to health, not only for the individual who smokes, but also for the people around the smokers due to inhalation of cigarette smoke. Tidal volume (VT) is the amount of air inhaled and exhaled when breathing while at rest. The normal tidal volume for someone with 70 kg body weight is between 350-400 ml. Objective: The aim of this research was to determine the correlation between smoking behaviors and lungs’ tidal volume of students of Nursing Sciences in Yogyakarta. Method: The method used in this research was descriptive correlation with a cross sectional approach. The samples for this research were selected using an accidental sampling technique, and 58 respondents were selected. The data for this research were collected by means of questionnaires and a spirometry, and the data collected were analyzed using a Kolmogorof Smirnov test. Result: In terms of smoking behaviors, the majority of smokers were students aged 22 years (20 students, or 67.2%), they belonged to medium category, a few of the students did not smoke (5 students, or 8.6%), 14 students were light smokers (32.8%), 4 students were heavy smokers (6.6%). The bivariate analyze was p-value<0.001. Conclusion: There is a correlation between smoking behaviors and lungs’ tidal volume of students of Nursing Sciences in Yogyakarta.